Gendering the REDD+ policy process in Ghana - Yeboah, Yaw (SLU/Dept. of Urban and Rural Development, 2013)
There is a growing discourse on ‘climate change’ resulting in consciousness of a world seen through the lens of climate. This has led to the development of new structures, actors as well as policies and programs at international, national and local levels with the aim of managing the implications that global warming and climate change might pose to the environment and humankind. REDD+ has emerged as a global policy instrument directed by policy makers at financing forest restoration and emission reduction activities undertaken by different players. Some actors have identified a need to include gender concerns in REDD+. In this thesis, I explore the process of designing a Gender Road Map as part of REDD+ policy formulation and its effects on forest policy in Ghana. How is gender being conceptualized and configured into national-local discussions as part of REDD+ policy build-up in Ghana? What strategies are used by different actors in the quest to mainstream gender? The thesis combines literature review, key informant interviews, semi-structured interviews, and focus group discussion and is based on explorative field studies which was carried out in Western Ghana in February and March, 2012.